(untitled) (Transport systems and technologies, 2022)
The article proposes a way to determine the position of the crew of the tape recorder using the method of rangefinder. The basis of the developed idea is the use of emitters with which you can register the rotational movements of the crew (pitch and dredging), as well as to register the roll. According to the results of the research, the following is substantiated: phase rangefinder with one emitter on the crew platform allows to determine the position of the crew on the race, its displacement in the horizontal plane relative to the longitudinal axis of the track structure and the height of the suspension between the crew bottom and three rotational movements (pitch, digging and roll). The novelty of the work is to substantiate the method of continuous positioning of high-speed magnetic levitation vehicle on 6 degrees of freedom based on phase rangefinder for arbitrary configuration in three-dimensional space of a fixed overpass and the integrity of the navigation system. The considered method of navigation is intended for use in high-speed transport ground systems on a magnetic suspension, the organization of the automated control of movement of wheeled transport on local platforms of industrial function, the organization of high-speed small-scale municipal transport of individual use.